Adoption of Omnichannel Technology along with its Impact on Customer Experience from an FMCG Perspective - Sharmila, R.; Bibiyana, D. Janis (International Review of Management and Marketing, 2026)
The use of omnichannel technology is becoming more important in improving customer experience with the fast-moving consumer goods (fmcg) segment that enables customers to utilize captive channels seamlessly either online or offline. This study explored the effects of three dimensions of technology adoption i.e. Channel synchronization, personalized marketing and technology integration on customer experience in a metropolitan retail setting in chennai, india. A cross-sectional study design was applied utilizing structured surveys and quantitative analysis was conducted to assess the direct association of technology adoption dimensions on customer experience. The results indicate that all three dimensions had a positive association with customer experience, with personalized marketing and technology integration having the most influence on customer experience, followed by channel synchronization. The study provides empirical evidence from an emerging market that reinforces the importance of aligned practices in technology adoption to enhance consumer engagement and offers implications for retailer managers in term of insights into technology investment allowing for the delivery of impactful customer experience.